Bridging the Gap: Knowledge, Awareness, and Practices on Vitamin D Deficiency among Adolescent and Young Adults – A Cross-Sectional Study - Elamin, Ali; Almalki, Basem; Adam, Hamza; Adam, Bhgah; Bakhsh, Reham; Otudi, Ahmed; Alhadri, Eissa; Homadi, Mazen; Zain, Khalid; Zakri, Albaraa; Al-Sumayli, Yahya; Abdelwahab, Siddig Ibrahim; et al. (International Journal of Child Health and Nutrition, 2025)
Background: Vitamin D deficiency is a significant public health issue, impacting bone health, immune function, and overall well-being. Despite abundant sunlight in Saudi Arabia, deficiency rates remain high, potentially due to limited sun exposure, cultural practices, and low dietary intake of vitamin D. University students are a key demographic for assessing public health awareness and behaviors related to vitamin D. This study aimed to assess the knowledge, attitudes, and practices (KAP) related to vitamin D deficiency among Jazan University students, and to identify demographic factors influencing these aspects. Methods: A cross-sectional study was conducted among 429 students at Jazan University, Saudi Arabia, from March to June 2024. Data on KAP regarding vitamin D deficiency were collected via a validated bilingual online questionnaire. Statistical analysis was performed using SPSS version 26, employing descriptive statistics and multivariate logistic regression to evaluate demographic predictors of KAP scores. Results: Among the participants, 47.3% exhibited high knowledge, 55% demonstrated high awareness, and 45.6% had high practice levels concerning vitamin D deficiency. Female students had significantly higher KAP scores than males (p < 0.01), and health college students showed greater knowledge and awareness than their non-health peers (p < 0.05). Multivariate analysis confirmed that gender was a significant predictor, with females displaying higher odds of better outcomes across all domains (Knowledge: AOR 2.66, 95% CI 1.73–4.07; Awareness: AOR 3.0, 95% CI 1.94–4.62; Practices: AOR 1.65, 95% CI 1.10–2.49). Conclusions: The findings highlight a need for targeted educational programs and routine screening initiatives to address vitamin D deficiency among young adults. Public health strategies should prioritize awareness campaigns across all academic disciplines to improve vitamin D literacy and mitigate deficiency-related health risks.